Intelligent Control of Robot Gripper Considering Feature Conditions - Hamzah, Ahmad; Rachel, Law Xian Hui; Mohd Razali, Daud (2014)
This paper deals with the analysis of three fingered robot manipulator to pick up objects intelligently with the appropriate force in order to avoid it damaging the object. In this project, three fingered gripper is designed to grasp an object without slipping or damaging the object with Fuzzy Logic approach. The fuzzy logic controller is used with many types of different membership types and number of fuzzy sets to evaluate the effect and performance of the grasping system. Based on the preliminary results, the triangular type of membership shows the simplest membership functions as the parameter are clear and easily understood and has faster computation time. However, the Gaussian membership shows better results when accuracy is considered.